Aortic root enlargement to mitigate patient–prosthesis mismatch: do early adverse events justify reluctance?. (20th February 2019) - Haunschild, Josephina; Scharnowski, Sven; Mende, Meinhard; von Aspern, Konstantin; Misfeld, Martin; Mohr, Friedrich-Wilhelm; Borger, Michael A; Etz, Christian D
Abstract: OBJECTIVES: Concomitant aortic root enlargement (ARE) at the time of surgical aortic valve replacement can be performed to avoid patient–prosthesis mismatch, an important predictor of adverse long-term outcome. METHODS: We performed a single-centre, retrospective analysis of 4120 patients receiving isolated aortic valve replacement, of whom 171 (4%) had concomitant ARE between January 2005 and December 2015. The analysis of postoperative outcome and early mortality was performed. Owing to inequality of the groups, patients were matched 1:1. RESULTS: The mean age of all 4120 patients was 68.8 ± 10.5 years, and comorbidities were equally balanced after matching. The mean aortic cross-clamp time, cardiopulmonary bypass time and total operative time were prolonged by 19, 20 and 27 min in the ARE group, respectively. Early mortality was not statistically significantly different with 1.4% in the surgical aortic valve replacement and 1.8% in the ARE group. Postoperative complications were <5% in all matched 338 patients: bleeding (3% vs 3%), pericardial effusion (3.0% vs 4.2%), sternal instability (1.8% vs 0%) and sternal wound infection (3.0% vs 1.2%). A significant higher number of patients had respiratory failure after ARE (unmatched: 17.1% vs 9.9%, P < 0.001; matched: 18.3% vs 9.5%, P = 0.028). Factors independently associated with overall mortality were age [hazard ratio (HR) 1.71], chronic obstructive pulmonary disease (HR 1.47), diabetes (HR 1.82), atrial fibrillation (HR 2.14) and postoperative respiratory failure (HR 2.84). CONCLUSIONS: ARE can be performed safely in experienced centres with no significant increase in the risk of early postoperative surgical complications and early mortality. However, the surgeon and the intensive care unit team should be aware of an increased risk for postoperative respiratory failure in ARE patients.